Mechanical particle properties - design, characterization and application - Romeis, Stefan; Peukert, Wolfgang; Paul, Jonas (International Conference for Conveying and Handling of Particulate Solids (CHoPS2015), 2015)
The (nano-)mechanics of particles across all length scales down to the nanoscale are highly relevant for many applications including adhesion, friction, powder flow, comminution and tribology. Nanomechanical elastic and inelastic particle properties have been measured systematically in a novel nanoindentation device installed within a scanning electron microscope to obtain simultaneously forcedisplacement information and optical images of deformed and broken particles. Quantitative data of intrinsic particle properties (and their respective distributions) are measured for oxide, metal and polymer particles. We discuss structure - property functions of particles in a quantitative way for selected applications, e.g. the production of bioactive glass and novel polymer particles in additive manufacturing.
Keywords: nano; mechanic; particle; powder; flow